Lideranças para a educação escolar: proposições em analise - Dalcorso, Claudia Zuppini (2019)
The present study aims to collaborate with the qualification of public education in Brazil, through the implementation of proposals of analysis that focus on the work and training of school managers. The aim is to improve the performance of these professionals as well as to enhance their respective competencies in the search for the resolution of flaws by adjusting them to the places where they operate. For that, this research identified contexts, methodologies and standards of professional competences in four training courses for school managers; it has analyzed related points by highlighting the cases of the four schools of studied school leaders, it has also raised proposals to inspire projects, courses and curricula that target school leaders. The chosen courses were: the Center for the Development of Educational Leadership (CEDLE) in Chile, the National College for School Leadership in England, the NYC Leadership Academy in New York City in the United States and the Management for Learning course in Brazil. By analyzing the competency standards of the courses, it was possible to elaborate a classification of the priority competences to be developed in the training of beginners or in-service managers, considering the ones that are repeated and intensified in the studies of the schools in comparison to the standards of competence of other places. It was possible to perceive the characteristic of a training focused on the practice of these professionals, as well as the use of methodologies that favor the accompaniment of an experienced mentor for the training of the beginning managers. The importance of considering the contexts of each studied area as a differential factor to understand their pathways was another fundamental point identified for the nonperformance in the error of disregarding this element in the intention of transferring the methodology to our reality